IMPROVING EWE OOCYTE VIABILITY AFTER VITRIFICATION WARMING USING COMBINATION OF DIFFERENT CRYOPROTECTANT AND CARRIER SYSTEM - Widyastuti, Rini; Setiawan, Rangga; Syamsunarno, Mas Rizky Anggun Adipurna; Ghozali, Mohammad; Saili, Takdir; Boediono, Arief (Jurnal Kedokteran Hewan, 2018)
The aim of this study was to determine the best combination of cryoprotectant (Ethylene glycol, EG), dimethyl sulfoxide (DMSO) and propanediol (PrOH) and carrier system (hemistraw and cryotop) in improving ewe oocytes viability during cryopreservation. Oocytes with multi layers of compact cumulus cells were colleted from abbatoir and matured in TCM 199 medium supplemented with 10% fetal calf serum for 24-26 h at 38.5 C under 5% CO2 in the air. Matured oocyte was divided into six parts and vitrified in three different vitrification solutions; (i) 17% EG+17% DMSO with hemistraw as carrier system, (ii) 34% EG with hemistraw as carrier system, (iii) 17% EG+17% PrOH in hemistraw (iv), 17% EG+17% DMSO with cryotop as carrier system (v), 34% EG with cryotop as carrier system (vi), and 17% EG+17% PrOH in cryotop. Oocytes were cryopreserved for one week before revived and evaluated for viability. The result showed that oocytes vitrified in media containing EG and DMSO in cryotop had the highest viability (88.16%) compared to media containing EG only or EG and PrOH (70.95% and 68.76%, respectively) (P0.05). Moreover, oocytes viability that vitrified using cryotop and hemistraw as carrier system were not significantly different. The present results indicated that vitrification using combination of EG and DMSO as permeable cryoprotectant and cryotop as carrier system was the best system to maintain oocyte viability after vitrification-warming.